A new species of Potamobates Champion from Colombia with a re-analysis of phylogenetic relationships (Hemiptera: Gerridae) - Padilla-Gil, Dora N.; Damgaard, Jakob (Zootaxa, 2011)
Potamobates tumaquensis n. sp. from Colombia is described and its phylogenetic relationships and biogeographical characteristics discussed. An updated identification key to Potamobates species is also provided.